Study on the state of the art of the “guiding image” – The rescue of a river's memory in favor of an urban river restoration project - Bahiana, Julia Roizemberg; Veról, Aline Pires (National Journal of City Management, 2020)
The progressive transdisciplinary discussion and the preference for an ecological restoration of degraded water courses over rigid engineering solutions currently influence the urban water management and the construction of a guiding reference image is indispensable for its realization. This review article discusses how this set of goals has been approached, in different fields of knowledge, derived from the term “guiding image”. As part of the technical literature about river restoration, the concept commonly alludes to the rescue of the memory of a river, even if the restoration of the original conditions is not part of the final project goal. This work is part of a larger research on the development of an adequate methodology to leverage the river restoration design, in which natural and urban demands coexist in a resilient state, while the river, as a natural element, has been lost and does not exist in collective memory. The various factors that make up the goals of a project of such complexity made up the questions from which this work was developed. As a result, a systematic literature review was carried out with the support of the free scientific search platform “Google Scholar”. Among the results, nine international theses, two books and seven journal articles were found. The research showed the similarities in the discussions and practices around the world, as well as the continuity of the concepts integrated to the reference image in the restoration project with ecological objectives.